2021
DOI: 10.1016/j.abd.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Ocular involvement in sporotrichosis: report of two cases in children

Abstract: Sporotrichosis is a subcutaneous mycosis that affects humans and animals, with a typically subacute or chronic evolution, caused by Sporothrix spp ., a dimorphic fungus. Although the cutaneous form is the most frequent presentation, the ocular involvement has been more frequently diagnosed in endemic areas, affecting mainly children and the elderly. Approximately 80% of affected patients have the lymphocutaneous form, while only 2.3% have conjunctival lesions, with 0.7% showing primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A total of 68 publications with 11,050 cases of sporotrichosis were found in South America [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 …”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 68 publications with 11,050 cases of sporotrichosis were found in South America [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 …”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
“…Of these, 4 reports were found in Argentina during the analyzed period with 38 cases, of which 9 were caused by S. schenckii sensu stricto (23.68%), 26 by S. brasiliensis (68.52%), 1 by S. globosa (2.6%), 1 by S. schenckii (2.6%), and 1 by S. schenckii complex (2.6%) [ 61 , 62 , 63 , 64 ]. Brazil reported 42 articles with 5546 analyzed cases [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ], identifying Sporothrix spp. and S. schenckii complex as the causative agent in 4906 cases (88.46%), S. schenckii in 302 (5.45%), S. brasiliensis in 125 (2.25%), Sporothrix sensu lato in 110 (1.98%), S. globosa plus S. schenckii in 91 cases (1.64%) Sporothrix sensu stricto in 5 (0.09%), S. globosa in 4 (0.07%), and S. mexicana in 3 (0.05%) during the studied period.…”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies (case reports and case series) reported ocular sporotrichosis with involvement of the conjunctiva, representing a total of 56 patients, with a mean age of 33.33 ± 21.81 years (range 3-80 years) (Table 3) [34,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Most cases have been reported in Brazil (44 cases) and Malaysia (8 cases).…”
Section: Conjunctival Sporotrichosismentioning
confidence: 99%
“…The left eye was more commonly affected than the right one (15 vs. 12 cases, respectively), although in 29 cases, the affected eye was not specified. S. schenckii was isolated in 25% of the cases (14 patients) [39][40][41]44,47,[50][51][52][53] followed by S. brasiliensis (5.3%, 3 cases) [26,45]; isolation was not achieved in 4 patients (7.4%) [3,4,7,11], and in 35 (62.5%), the species involved was not determined [12,34,37,38,43,49]. Previous trauma related to conjunctival implantation was not reported in any patient, although contact with cats was reported in 50 patients (89.3%) (Table 3) [26,34,37,38,40,41,[43][44][45][46][47][48][49][50][51][52][53].…”
Section: Conjunctival Sporotrichosismentioning
confidence: 99%